Identification of co-expressed central genes and transcription factors in atherosclerosis-related intracranial aneurysm - Zhang, Quan; Liu, Hengfang; Zhang, Min; Liu, Fang; Liu, Tiantian (Frontiers in Neurology, 2023)
Background: Numerous clinical studies have shown that atherosclerosis is among the risk factors for intracranial aneurysms. Calcifications in the intracranial aneurysm walls are frequently correlated with atherosclerosis. However, the pathogenesis of atherosclerosis-related intracranial aneurysm remains unclear. This study aims to investigate this mechanism. Methods: The Gene Expression Omnibus (GEO) database was used to download the gene expression profiles for atherosclerosis (GSE100927) and intracranial aneurysms (GSE75436). Following the identification of the common differentially expressed genes (DEGs) of atherosclerosis and intracranial aneurysm, network creation of protein interactions, functional annotation, identification of hub genes, and co-expression analysis were conducted. Then, we predicted the transcription factors (TF) of hub genes and verified their expressions. Results: A total of 270 common DEGs (62 down-regulated, 208 up-regulated) were identified for subsequent analysis. Functional analyses highlighted the significant role of phagocytosis, cytotoxicity, and T cell receptor signaling pathways in this disease's progression. Eight hub genes were identified and verified, namely, CCR5, FCGR3A, IL10RA, ITGAX, LCP2, PTPRC, TLR2, and TYROBP. Two TFs were also predicted and verified, which were IKZF1 and SPI1. Conclusion: Intracranial aneurysms are correlated with atherosclerosis. We identified several hub genes for atherosclerosis-related intracranial aneurysms and explored the underlying pathogenesis. These discoveries may provide new insights for future experiments and clinical practice.